Fintech, financial constraints and innovation: Evidence from China - Ding, Na; Gu, Leilei; Peng, Yuchao (Journal of Corporate Finance, 2022)
We examine how fintech development affects corporate innovation. Using the city-level fintech index that includes 331 cities, which is constructed based on data from Ant Finance Service Group, we identify the economic mechanisms through which fintech development affects technological innovation. We show that firms that are more financially constrained exhibit a disproportionally higher innovation level in cities with better developed fintech services. We further find that fintech development promotes lending to firms and stimulates R&D investment because internet credit intensifies bank loan competition. Our paper provides new insights into the effects of fintech development on the real economy.